Restoring the Health of Paddy Soil by Using Straw Compost and Biofertilizers to Increase Fertilizer Efficiency and Rice Production with Sobari (System of Organic Based Aerobic Rice Intensification) Technology - Turmuktini , Tien; Kantikowati , Endang; Natalie, Betty; Setiawati, Mieke; Yuwariah, Yuyun; Joy , Benny; Simarmata , Tualar (Asian Journal of Agriculture and Rural Development, 2012)
Current conditions indicate that about 70% of paddy fields in Indonesia has been experiencing severe degradation of land and can be categorized as an illness (sick soils), therefore, efforts to restore health and increase the productivity of paddy soil in a sustainable manner can be done by integrating fertilizer-based integrated management organic and biological fertilizers (biofertilizers) with SOBARI (system of organic based aerobic rice intensification )technology. The experiment was conducted from March to August 2011 in the fields eksperiment Faculty of Agriculture Padjadjaran University, Bandung with the aim of testing the use of straw compost + biofertilizer for efficientcy inorganic fertilizer (N, P, K) and increase rice production by SOBARI technology. Experiments was using a split plot design. The main plot consists of 8 standard combination of organic fertilizer (compost straw 0: 2.5: 5.0 and 7.5 t ha-1, with no biological fertilizers and biological fertilizers 400 g ha -1. Sub plots consisted of 5 standard: organic fertilizer N, P and K (100%, 90%, 80%, 70% and 60% of recommended dosage). The results are: interaction occur between the provision of straw compost + biofertilizer, to the yield per plot. Dosage of 5.0 t ha -1 of compost straw + 400 g ha-1 biological fertilizer by accompanied N, P, K 80% of the recommended, may show the highest yields and increase the yield of 13.3% compared to controls is 7.29 kg plot -1(6.654 t ha -1) and gained efficienciy fertilizer N, P, K 20%, of the recommendation.